Analysis in the Strategic Formula for Business and Information Technology Alignment of the Research and Development Planning Institution in Batu City - Musthafawi, Aulia Zahra; Aknuranda, Ismiarta; Ramdani, Fatwa (Faculty of Computer Science (FILKOM) Brawijaya University, 2020)
The Batu City Area Research and Development Development Planning Institution (Badan Perencanaan Pembangunan Penelitian dan Pengambangan Daerah-Bappelitbangda) is one of the important regional apparatus organizations for the Batu city government. However, in carrying out its performance, Bappelitbangda still faces difficulties in several cases in monitoring the vision and mission achievement, for instance; the reporting that is often not in accordance with the results achieved and not evaluating the achievement of indicators in the regional apparatus organizations that do not reach the target. The difficulty is due to the lack of technology's role in supporting Bappelitbangda's performance so that the objectives to be achieved are not maximal. To resolve this, it is necessary to have strategic planning of the information system that can help Bappelitbangda achieves the goals. The method proposed in this study is by adapting the strategic planning method that starts by analyzing both the internal and external environment in terms of business or term of Information Systems (IS)/Information Technology (IT) and also the SWOT analysis. The results of this study could be the proposals for business IS strategies, IT strategies and IS/IT management strategies. The objectives as well as the new strategic formulas analysis based on SPBE which are expected to help Bappelitbangda harmonize the technology utilization.